In vitro somatic embryogenesis and adventitious root initiation have a common origin in eggplant (Solanum melongena L.) - Tarré,Erika (2004)
Somatic embryogenesis was induced from cotyledon explants of eggplant cultured on MS medium supplemented with 54 µM NAA. Anatomical analysis of somatic embryo initiation and development was performed during the first four weeks. Proembryo formation was observed after the second day of culture, directly from perivascular cells or via pro-embryogenic masses derived from indeterminate meristematic masses (IMMs) originated in the vascular tissue. Those IMMs also gave rise to root primordia after 10 days of culture. The origin of embryos is discussed as well as the similarities between somatic embryogenesis and adventitious root formation.